An analysis of slang words found in the song lyrics of katy perry mtv unplugged album - Nopitasari, Ni Kadek Mega Sintya; Jendra , I Made Iwan Indrawan; Santika, Dewa Ayu Devi Maharani (Institut Pariwisata dan Bisnis Internasional, 2022)
Slang is very informal language or specific words used by a particular group of people. Slang words are usually spoken more often in emails or other written text. This included song lyrics. The study aims to analyze the types of slang and the meaning of slang words from the song lyrics of Katy Perry songs in MTV Unplugged album. This study used a descriptive qualitative method. The selected song lyrics by Katy Perry were chosen as the data source. Descriptive study in textual analysis is applied to elaborate the types and meaning which occur in song lyrics on MTV Unplugged Album. The theory proposed by Partridge (1984) was referred to analyzing the types of the slang words and the theory proposed by Leech (1981) for the meanings of the words. Based on the data were 16 words of society slang, slang in theater have 1 data, cockney slang have 2 data, public house slang have 1 data and 1 data from slang in art. Meanwhile, based on the theory of Leech (1981) this study found conceptual meaning occurred with 14 data, connotative meaning occurred with 6 data, and reflected meaning occurred with 1 data. There is no data that can be classified into social meaning, affective meaning, collocative meaning, and thematic meaning.